Knocking on Labor's Door : Union Organizing in the 1970s and the Roots of a New Economic Divide - Windham, Lane (Book collections on Project MUSE., 2017)
Highlighting the integral, often-overlooked contributions of women, people of color, young workers, and Southerners, Lane Windham reveals how in the 1970s workers combined old working-class tools - like unions and labour law - with legislative gains from the civil and women's rights movements to help shore up their prospects.